WAJIB BELAJAR 9 (SEMBILAN) TAHUN TERHADAP ANAK YANG DIJATUHKAN PIDANA DENGAN SYARAT BERDASARKAN UU NO. 11 TAHUN 2012 TENTANG SITEM PERADILAN PIDANA ANAK - Anugrah Ashriany (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT Analysis to 9 (nine) years education compulsory for children with requirements under the criminal law - law number 11 of 2012 about the Juvenile Justice System, advised by Kunti Widayati, SH, M. Hum, as a supervisor I and Ony Rosifany SH, M. Hum as Supervisor II.Penalty clause is one of the ways which the application of criminal supervision and implementation is done outside the prison, while the requirements for implementing the penalty clause is required to attend the 9 (nine) years education compulsory as mentioned in chapter 73 article (8) Constitution of Juvenile Justice System.The program of education compulsory to fulfill the state's responsibility in terms of education services is one of the requirements that must be implemented to children in conflict with the law under the supervision of the Public Prosecutor and guided by Supervisor Society.The 9 (nine) years education compulsory activities to children with sentenced to penalty clause handled by the Education Department in collaboration with several agencies such as the Social Service District City, KPAI Province, Central Office of Correctional Class II, the Court, the Prosecutor and the local police.It is recommended to do enhancement and improvement of coordination between relevant institutions that deal with children in conflict with the law to increase the 9 (nine) years education compulsory program of children with penalty clause.   Keywords :children, education, criminal, law